دراسة مقارنة لدرس التربية الرياضة في المدارس الاحادية والمزدوحة الدوام لدى طلاب المرحلة المتوسطة في بغداد - فراس طلعت حسين (الرياضة المعاصرة)
Abstrcat The research problem Tkamin there are a lot of schools do not pay attention to studying , especially in schools double any discrepancies in Give Lesson between schools , resulting in weakness and a decline in fitness among students and shows that Bodh through work during the physical education lesson The objectives of research knowledge level the differences for education lesson sport between schools unilateralism and double, and the researcher used the descriptive way of comparison, the sample consisted students from the stage average in the province of Baghdad schools unilateralism and double time , and numbered (300) students were chosen randomly , the researcher used battery Aorofitnes tests to conduct among the students to extract the results, and it was the most important findings increase the number of hours devoted to physical education lesson in school monounsaturated helped in the progress of these schools on the Schools double in addition to the always comforting helped schools unicycle progress in recipes for fitness because of the lessons of regular physicale ducation lesson in table weekly